2021
DOI: 10.29309/tpmj/2021.28.03.6309
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of port site infection following gall bladder removal through Epigastric vs Umbilical port.

Abstract: Objective: To compare the frequency of port site wound infection following gall bladder removal through umbilical and epigastric port in laparoscopic cholecystectomy. Study Design: Randomized Control Trial. Setting: Surgical Unit 2, Ghulam Muhammad Mahar Medical College, hospital Sukkur. Period: 1st November 2019 to 30th October 2020. Material & Methods: All cases who underwent four port laparoscopic cholecystectomy were enrolled in two groups. All procedures were performed under general anesthesia. As the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Patients with PSI had higher BMI than those who did not develop PSI. A similar observation has been reported in a local study which demonstrated that patients with higher BMI had higher frequencies of PSI in their trial (17).…”
Section: Figure 1 Gender Distributionsupporting
confidence: 88%
“…Patients with PSI had higher BMI than those who did not develop PSI. A similar observation has been reported in a local study which demonstrated that patients with higher BMI had higher frequencies of PSI in their trial (17).…”
Section: Figure 1 Gender Distributionsupporting
confidence: 88%